2008
DOI: 10.1002/ana.21331
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin prevents epilepsy in a mouse model of tuberous sclerosis complex

Abstract: Rapamycin has strong efficacy for preventing seizures and prolonging survival in Tsc1(GFAP)CKO mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
552
6
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 575 publications
(608 citation statements)
references
References 32 publications
27
552
6
10
Order By: Relevance
“…It was diluted in 5% Tween 80, 5% polyethyleneglycol 400 and 4% ethanol immediately before use 18. Rapamycin was injected intraperitoneal once a day at the dose of 3.0 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…It was diluted in 5% Tween 80, 5% polyethyleneglycol 400 and 4% ethanol immediately before use 18. Rapamycin was injected intraperitoneal once a day at the dose of 3.0 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Rapamycin inhibits seizures and mTOR pathway activation in a mouse model of the TS complex [101,[103][104][105], And also improved cognitive outcome in a rat model of infantile spasms [104].…”
Section: New Optionsmentioning
confidence: 99%
“…These genes, known as tumour suppressors, are responsible for the inhibition of the mammalian target of rapamycin (mTOR) signalling pathways [100]. Mutations in these genes cause hyperactivation of the mTOR system and result in excessive cell growth and hamartomatous tumours in multiple organs [100,101]. Recently, novel treatment with mTOR inhibitors proved to be effective in the suppression of progressive proliferative growth of subependymal giant cell astrocytoma (SEGA) and renal angiomyolipomas [102].…”
Section: Tuberous Sclerosis (Ts)mentioning
confidence: 99%
“…Furthermore, Zeng et al [20] found that rapamycin exerted an anti-seizure effect in a mouse model of tuberous sclerosis-a disease in which there is strong evidence supporting a role for the hyperactivation of the mTOR pathway in the pathology of tuberous sclerosis. Unfortunately, the initial observations suggesting that rapamycin prevents SE-induced mossy fiber sprouting were contingent upon the continued exposure to rapamycin.…”
Section: Definitionsmentioning
confidence: 99%